Attitudes and occupational sex-role stereotypes relating to natural science studies in higher education among rural Black females - Makate, Paulina Pulane (University of the Free State, 2009)
English: The purpose of the study was to investigate the relationship between science attitudes, occupational sex-role stereotypes and the entrance of rural Black females into natural science studies in Higher Education (HE). Through this process it was endeavoured to shed light on the factors that deter Black females from pursuing science studies or following careers in the natural sciences. The sample consisted of 112 Black female grade 12 learners from 5 rural schools in the Xhariep district Free State. Marks obtained in biology, physical science and mathematics were regarded as the criterion for entrance to natural science studies. The marks were obtained from the results of the Grade 11 examinations of November 2008. The standardised measuring instruments used in this quantitative study were the Science Attitude Scale for Middle School Students and the Occupational Sex-Role Stereotype Questionnaire. Data was analysed using univariate and multivariate statistics. Results in this study revealed that the academic achievements of Black Grade 12 female learners in biology, physical science and mathematics were poor in Grade 11. The results showed that there were no significant relationships between science attitudes, occupational sex-role stereotypes and the marks in biology, physical science and mathematics. All P-values were greater than 0.05. In the case of marks in biology and physical science, the confounding variables (ethnicity, age and psychosocial factors) did not have a significant effect on the dependent variable. However, in respect of the dependent variable (marks in mathematics), age and psychosocial background factors both had a significant effect, but not ethnicity. It was interesting to note that ethnicity was not a significant confounder, because the P-value was greater than 0.05. However, the t-test indicated that the performance of Xhosa females in science (consisting of their total marks in biology, physical science and mathematics) was better than that of the South Sotho females. Recommendations for various stakeholders were presented. They include: creating classroom environments that spark initial curiosity and foster long-term interest in biology, physical science and mathematics, providing spatial skills training, helping learners to structure appropriate study habits and to develop identities as learners, exposing learners and students to laboratory work in university chemistry and in schools, increasing parental involvement, providing teachers with mentorship programmes in the teaching and learning of biology, physical science and mathematics, preparing secondary school learners for higher education and improving educator qualifications in biology, physical science and mathematics.

Afrikaans: Die doel van die studie was om die verwantskap tussen houdinge jeens die natuurwetenskappe, beroepsgeslagsrol-stereotipes en die toetrede van plattelandse Swart vroulike leerders tot natuurwetenskaplike studies aan hoer onderwysinstellings te ondersoek. Op hierdie wyse is gepoog om meer lig te werp op faktore wat vroulike persone in Suid-Afrika moontlik verhinder om sodanige studies te volg of tot loopbane in natuurweteskaplike beroepe toe te tree. Die steekproef het bestaan uit 112 Swart vroullike graad12-leerders uit vyf plattelandse skole in die Xhariep-distrik in die Vrystaat. Die punte wat behaal is in biologie, natuur- en skeikunde en wiskunde is beskou as die kriterium vir toetrede tot natuurwetenskapstudies. Die punte is verkry uit die resultate vir die graad 11-eksamen van November 2008. Twee verskillende gestandaardiseerde vraelyste is in hierdie kwantitatiewe studie gebruik, naamlik die Science AttitudeScale for Middle School Students en die Occupational Sex-Role Stereotype Questionnaire. Die data annalise is gedoen deur middel van eenfaktor ontledings en meervoudige variansie analises. Die resultate van die studie toon dat die akademiese prestasie van vroulike Swart graad 12-leerders in biologie, natuur- en skeikunde en wiskunde in graad 11 swak was. Die resultate toon egter dat daar geen beduidende verwantskap is tussen houdinge jeens die natuurwetenskappe, beroepsgeslagsrol-stereotipes en die totale punte behaal in biologie, natuur-en skeikunde en wiskunde nie. Alle P-waardes was groter as 0.05. Ten opsigte van punte vir biologie en natuur- en skeikunde het die strengelingsveranderlikes (etnisiteit, ouderdom en psigososiale faktore) nie ’n beduidende effek op die afhanklike veranderlike gehad nie. Ten opsigte van die afhanklike veranderlike (wiskundepunte) het ouderdoms- en psigisosiale agtergrondfaktore wel albei ’n beduidende effek getoon, maar etnisiteit nie. Dit was interessant om waar te neem dat etnisiteit nie ’n beduidende strengelaar is nie, want die P-waarde was groter as 0.05. Die t-toets toon egter dat die prestasie van vroulike Xhosa-persone in wetenskap (bestaande uit hul totale punte in biologie, natuur- en skeikunde en wiskunde) beter was as dié van vroulike Suid-Sotho-leerders. Aanbevelings vir verskillende belangegroepe word aangebied. Dit sluit in: die skep van klaskameromgewings wat aanvanklike nuuskierigheid prikkel en langtermyn-belangstelling in biologie, natuurkunde en wiskunde bevorder, opleiding in ruimtelike vaardighede, hulp aan leerders om toepaslike studiegewoontes aan te leer en hul leerderidentiteit te ontwikkel, blootstelling van leerders en studente aan laboratoriumwerk in chemie en fisika op universiteit en op skool, verhoogde ouerbetrokkenheid, mentorskapprogramme vir onderwysers in die onderrig en leer van biologie, natuur- en skeikunde en wiskunde, voorbereiding van leerders in die sekondêre skool vir hoër onderwys en die verbetering van opvoeders se kwalifikasies in biologie, natuur- en skeikunde en wiskunde.
Keywords: Natural science studies; Science attitudes; Occupational sex-role stereotypes; Academic achievements; Black learners; Female learners; Ethnicity; South Africa; Free State; School teaching; College students--South Africa--Attitutudes; College students -- Education (Higher) -- South Africa; Educational surveys--South Africa; Women college students -- South Africa; Science -- Study and teaching (Higher) -- South Africa; Thesis (Ph.D. (Higher Education Studies))--University of the Free State, 2009